Union catalog of medical and paramedical resources in five government hospital libraries in Quezon City - Maramag, Araceli B. (1978)
A listing by subject and by author/title of 2,980 books, periodicals, and special materials/publications available at the libraries of five government hospitals was completed in this study. These hospitals which recently formed an administrative alliance to improve their present systems and services are the Armed Forces of the Philippines Medical Center, Government Service Insurance System General Hospital, National Orthopedic Hospital, Philippine Heart Center for Asia, and Veterans Memorial Medical Center.